Behavioral Activation Therapy to Reduce Withdrawal Behavior In Schizophrenia Patients - Larasati, Nurul Afifah; Ananta, Aliffia (Kirana Publisher (KNPub), 2025)
This study was based on observations of a male patient with schizophrenia who was staying in a mental hospital. The patient displayed withdrawn behavior and tended to avoid interacting with other patients in the ward. If left untreated, this pattern of behavior could interfere with the patient’s recovery, as he showed no interest in doing anything except lying in bed and staying in the corner of the room. The purpose of this study was to reduce the patient’s withdrawn behavior by increasing his involvement in daily structured activities. This research applied an experimental approach using a single-subject design. Data were collected by observing the patient’s participation in scheduled therapeutic activities. A behavior monitoring sheet was used to compare the subject’s behavior before and after the intervention. The results showed that Behavioral Activation Therapy (BAT) was quite effective. After the intervention, the patient began engaging in more activities, which contributed to a noticeable reduction in his withdrawn behavior.